2006
DOI: 10.1017/s0954579406060494
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and measurement issues in the assessment of pediatric bipolar disorder: Implications for understanding mood disorder across the life cycle

Abstract: The goal of this paper is to review assessment research of bipolar disorder in children and adolescents. The review addresses numerous themes: the benefits and costs of involving clinical judgment in the diagnostic process, particularly with regard to diagnosis and mood severity ratings; the validity of parent, teacher, and youth self-report of manic symptoms; how much cross-situational consistency is typically shown in mood and behavior; the extent to which a parent's mental health status influences their rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 144 publications
0
37
0
Order By: Relevance
“…While the YMRS has normative data in ADHD populations showing that most children with ADHD will not score in the elevated range Fristad et al 1992;Youngstrom et al 2002), it was not designed to identify manic symptoms in children with ADHD. Most rating scales of pediatric BP are plagued by similar limitations due to the inherent difficulties with separating ODD ϩ ADHD from BP at a single time point (Pavuluri et al 2006;Youngstrom et al 2006).…”
Section: Limitationsmentioning
confidence: 99%
“…While the YMRS has normative data in ADHD populations showing that most children with ADHD will not score in the elevated range Fristad et al 1992;Youngstrom et al 2002), it was not designed to identify manic symptoms in children with ADHD. Most rating scales of pediatric BP are plagued by similar limitations due to the inherent difficulties with separating ODD ϩ ADHD from BP at a single time point (Pavuluri et al 2006;Youngstrom et al 2006).…”
Section: Limitationsmentioning
confidence: 99%
“…Most experts recommend that assessment of child and adolescent problems include information from the child and parent(s), but significant discrepancies between parent-and child-report are often found (Achenbach et al 1987;De Los Reyes and Kazdin 2005). With respect to the diagnosis of bipolar disorder, Youngstrom et al (2006) found that assessment measures completed by parents provided better information about manic symptoms than child-or teacher-report measures. Moreover, combining information from multiple informants did not provide additional information.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, severity of illness impacts treatment outcome in ADHD (Hinshaw 2007) and depression (Curry et al 2006). researchers differ on how they elicit, assess, characterize, and count criteria (Youngstrom et al 2006). The degree to which these decisions influence their sample selection and ultimate findings is unclear (Galanter et al 2008).…”
Section: Topic #1: Definition and Assessment Of Bpmentioning
confidence: 99%
“…What has complicated work up to now is that investigators say they are using the same criteria, methods, and terms but use and define them differently (Youngstrom et al 2006). …”
Section: Aacap 2006 Research Forummentioning
confidence: 99%